Variations in the hospital management of self-harm and patient outcome: A multi-site observational study in England. - Cooper, J; Steeg, S; Gunnell, D; Webb, R; Hawton, K; Bennewith, O; House, A; Kapur, N (Elsevier, 2014)
INTRODUCTION: Studies have shown wide variations in delivery of self-harm services but it is unclear how these relate to important outcomes such as self-harm repetition. METHODS: Data were collected on self-harm presentations and hospital management from 31 hospitals in England. Key staff were interviewed about service provision for self-harm patients and responses were mapped to a 21-item service quality scale. Our main outcome was repeat hospital-presenting self-harm within six months. RESULTS: 6347 individuals presented with 7599 episodes of self-harm during a three month period in 2010-2011. Re-attendance with self-harm within six months of index episode occurred in 21% (1308/6347) of individuals (range between hospitals 9-27%). We found little association between clinical management at hospital level (i.e. proportion of episodes receiving psychosocial assessment, medical or psychiatric admission, and referral to statutory or non-statutory services) and repetition rate. The median score on service quality scale was 14.5 (range between hospitals 10.5-19). There was no evidence of correlation between total service quality score and repetition of self-harm (Spearman׳s r=-0.06, p=0.73) or between individual service items and repetition. LIMITATIONS: We did not explore certain aspects of service provision e.g. quality of psychosocial assessments and length of admission. Hospital presentation for repeat self-harm may not be the most reliable measure of service quality. CONCLUSION: At aggregate level aspects of management and service structures did not appear to be associated with self-harm repetition rates. Future research should focus on better understanding the processes underlying the delivery of services at hospital level and their relationship to outcome.